2009
DOI: 10.14210/bjast.v13n1.p19-24
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of sodium edta and heparin as anticoagulants for the evaluation of haematological parameters in cultured and feral african catfish (Clarias gariepinus)

Abstract: The anticoagulants used in this study were lithium heparin and sodium ethylenediaminetetraacetic acid (EDTA). Red blood cell (RBC) count, packed cell volume (PCV), hemoglobin concentration (Hb), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), total white blood cell (WBC) count and differential count were determined. No significant differences (p >0.05) were observed in the total RBC, WBC and MCHC values in the feral and pond cultured fish. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
2
9
1
Order By: Relevance
“…The fish were anaesthetized before blood sampling using 2‐phenoxyethanol (99%; MERCK, Whitehouse Station, NJ, USA) at the concentration of 400 mg⋅l −1 and successively underwent to venipuncture for blood collection. Blood samples were obtained by puncturing the caudal vein using a 20 × 1½‐gauge syringe and collected in microtubes (Miniplast 0.6 ml, LP Italiana Spa, Milano) containing ethylenediaminetetraacetic acid (ratio, 1.26 mg/0.6 ml) as the anticoagulant agent . The time between capture and blood sampling was less than 3 min.…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…The fish were anaesthetized before blood sampling using 2‐phenoxyethanol (99%; MERCK, Whitehouse Station, NJ, USA) at the concentration of 400 mg⋅l −1 and successively underwent to venipuncture for blood collection. Blood samples were obtained by puncturing the caudal vein using a 20 × 1½‐gauge syringe and collected in microtubes (Miniplast 0.6 ml, LP Italiana Spa, Milano) containing ethylenediaminetetraacetic acid (ratio, 1.26 mg/0.6 ml) as the anticoagulant agent . The time between capture and blood sampling was less than 3 min.…”
Section: Methodscontrasting
confidence: 99%
“…Blood samples were obtained by puncturing the caudal vein using a 20 Â 1½-gauge syringe and collected in microtubes (Miniplast 0.6 ml, LP Italiana Spa, Milano) containing ethylenediaminetetraacetic acid (ratio, 1.26 mg/0.6 ml) as the anticoagulant agent. 25 The time between capture and blood sampling was less than 3 min. All samples were analyzed immediately (T 0 ) by both a manual and automatic method.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations beyond 2 mg/ml of blood are reported to produce significantly lower values of PVC and higher MCHC, which indicates cell shrinkage and morphological degeneration (Bain et al 2016). An increase in red blood cell volume is thought to be a response to stress due to a variety of factors (Adeyemo et al 2009). Calcium in the nucleated erythrocyte extracellular environment is vital for the maintenance of membrane integrity (Witeska and Wargocka 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Cells reaction of various animal species to anticoagulants may be different. Studies on several fish have found that blood cells were unaffected by EDTA, heparin or sodium citrate but both EDTA and citrate reduced white blood cell viability (Walencik and Witeska, 2007;Adeyemo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of various types of anticoagulants in hematology were studied in various fish species (Walencik and Witeska, 2007;Witeska and Wargocka, 2011;Ekanem et al, 2012;Adeyemo et al, 2009) but no information's for M. cephalus hematology were found.…”
Section: Introductionmentioning
confidence: 99%